2018
DOI: 10.1007/s10433-018-0459-2
|View full text |Cite
|
Sign up to set email alerts
|

Parental health limitations, caregiving and loneliness among women with widowed parents: longitudinal evidence from France

Abstract: We investigate how daughters’ feelings of loneliness are impacted when widowed parents develop health limitations, and when daughters take on personal care tasks in response. Using longitudinal data from daughters of widowed parents drawn from the French Family and Intergenerational Relationships Study (ERFI, 1485 observations nested in 557 daughters), we assess (a) whether health limitations of widowed parents are associated with daughters’ feelings of loneliness regardless of whether or not daughters provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…According to the FCA, productivity costs only occur during the period necessary to fill the vacancy that has arisen due to sick leave, i.e. the friction period [ 18 ]. Therefore, instead of using a maximum of 2 years of sick leave, a friction period was used to which the number of sick leave days were limited.…”
Section: Methodsmentioning
confidence: 99%
“…According to the FCA, productivity costs only occur during the period necessary to fill the vacancy that has arisen due to sick leave, i.e. the friction period [ 18 ]. Therefore, instead of using a maximum of 2 years of sick leave, a friction period was used to which the number of sick leave days were limited.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, all time-invariant characteristics, including those not observed, were accounted for (Allison, 2009). This makes our estimates of the effects of providing care to ageing parents on quality of life not prone to bias due to omitted variables that are constant over time (Taylor et al , 1995; Kaschowitz and Brandt, 2017; Van den Broek and Grundy, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Our definition of care-giving requires that the parent to which the child provides assistance is in less than good health, and several studies have shown that parental health limitations are associated with poorer mental wellbeing of their children, regardless of whether or not care is provided to the parent (Amirkhanyan and Wolf, 2006; Wolf et al , 2015; Van den Broek and Grundy, 2018). We therefore included a dummy variable indicating that at least one living parent reportedly had ‘fair’ or ‘poor’ health, as opposed to ‘excellent’, ‘very good’ or ‘good’ health.…”
Section: Datamentioning
confidence: 99%
“…Still, research suggests that the effects of caregiving could differ based on a country's approach to long-term care. For example, countries with more generous long-term care policies tend to have higher levels of caregiver wellbeing (Bom & Stöckel, 2021;Brenna and Di Novi, 2016;Uccheddu et al, 2019;Van den Broek and Grundy, 2018). These differences may, in part, be due to the specialization theory outlined by Brandt (2013), which suggests that generous welfare states enable an effective division of labor between informal and formal care services.…”
Section: Caregiving Contexts: Long-term Care Policymentioning
confidence: 99%